2015
DOI: 10.1007/s10846-015-0271-6
|View full text |Cite
|
Sign up to set email alerts
|

Visual Based Landing for an Unmanned Quadrotor

Abstract: One of the main challenges for Unmanned Aerial Systems (UAVs) is to extend the endurance of small vehicles such as multi-rotors. Actually, Li-po batteries that guarantee a flight of about 20 minutes power this type of vehicles. The endurance can be extended by enabling vehicles to look for recharging station(s). In this paper, we propose a vision system able to detect and track a given pattern hosted on the target-landing platform. The pattern is also useful to estimate the UAV position while approaching the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Landing UAVs on a service charging station is realized with the help of various systems of navigation and analysis of the surrounding area. The paper [8] describes the vision system developed for target detection and tracking. Adopted an optimized solution to save computation time ensuring a real time image processing supported by the robot operating system environment.…”
Section: Electromechanical Maintenance Systems For Unmanned Aerial Vementioning
confidence: 99%
“…Landing UAVs on a service charging station is realized with the help of various systems of navigation and analysis of the surrounding area. The paper [8] describes the vision system developed for target detection and tracking. Adopted an optimized solution to save computation time ensuring a real time image processing supported by the robot operating system environment.…”
Section: Electromechanical Maintenance Systems For Unmanned Aerial Vementioning
confidence: 99%
“…Jeon et al [10] presented a real-time visionguided control algorithm (detection and tracking) for an UAV using CUDA-enabled GPU cards. Cocchioni et al [11] also showed the implementation of visual-based landing for an unmanned quadrotor using a NVIDIA Tegra Jetson K1.…”
Section: Introductionmentioning
confidence: 99%
“…Vision-Based Control: The aircraft's position and orientation are controlled on the basis of the information captured by vision sensors and subsequently processed by computer vision algorithms (e.g., [20][21][22]). The vision-based control of UAVs began in the 1990s.…”
mentioning
confidence: 99%
“…List of the most popular publication venues.Journal of Intelligent & Robotic Systems23 15.97%[18,20,27,30,40,51,68,69,71,73,[83][84][85][86][87][88][89][90][91][92][93][94][95] …”
mentioning
confidence: 99%